Implementation care nursing child: Hyperbilirubinemia - Kansia Anastasia Terok; Henny Pongantung; Vina Putri Patandung; Enjelita Karujan; Umboh Morenita Jeanifer (Institute of Computer Science (IOCS), 2026)
Hyperbilirubinemia is a condition characterized by elevated bilirubin levels in newborns that clinically appear as jaundice. This study aimed to describe the implementation of nursing care in newborns diagnosed with hyperbilirubinemia in a hospital setting. A descriptive case study approach was used involving three newborns with hyperbilirubinemia treated at Gunung Maria General Hospital, Tomohon, in March 2024. Data were obtained through comprehensive nursing care processes including assessment, nursing diagnosis, planning, implementation, and evaluation. The findings indicated that the infants experienced neonatal jaundice accompanied by hyperthermia, risk of impaired skin integrity, risk of infection, and parental anxiety. Nursing interventions were carried out through phototherapy management, breastfeeding education, hyperthermia management, infection prevention, and maintenance of skin integrity. After four days of nursing care, bilirubin levels decreased and the identified nursing problems showed improvement. The implementation of nursing care, particularly phototherapy combined with supportive interventions, contributed to the improvement of the infants’ condition and reduction of bilirubin levels.